EFFECTS OF FACEBOOK ON EXAM PERFORMANCE OF SOCIAL SCIENCES STUDENTS: A CASE STUDY OF THE UNIVERSITY OF MALAKAND - Khan, Asif Nawaz; Ali, Sajjad; Amin, Salman; Irfan, Muhammad (Humanities & Social Sciences Reviews, 2021)
Purpose of the Study: As various researchers found, Facebook is one of the most popular social media platforms among students. The purpose of this study was to assess the effect of Facebook on students’ exam performance. Methodology: For this Study, data was collected from the regular students of BS social sciences at the University of Malakand. The researcher used quantitative methodology to obtain fruitful results. A questionnaire was designed to assess the effect of Facebook usage on students, and data was collected from 182 students’ by simple random sampling technique. The analysis of the results was carried out through Statistical Package for Social Sciences (SPSS). Main Findings: The Study found that the Usage of Facebook affects students’ exam performance in Malakand. The study’s results supported the hypothesis that the more the students used Facebook, their exam performance would be poor. Application of the Study: This Study is essential to encourage students, parents and teachers to use Facebook for educational and learning purposes because most students use it for leisure time and relaxation. This study will help the students to manage Facebook usage time during exam days and to use it for refreshing and revealing boredom. It will help aware teachers and parents about the adverse effects of Facebook. The study will contribute a little to the existing literature gap on understanding the hurdle and blessing opportunities of Facebook in the exam environment. The study’s novelty: This is an exciting study involving university students and will discover the effects of Facebook on exam performance. The study will be helpful by bringing awareness among university students that Facebook Usage affects their exam performance. The study will also find out the relationship between Facebook usage and achievements in the exam. The students will come to know how spending more time on Facebook during exam days will affect their studies.